Stock Valuation of IDX ESG Leaders Constituents and Its Implications for Sustainable Economic Development in Indonesia (2020–2024) - Judandi Rizky Pratomo; Moh. Huzaini; Muhamad Bai’ul Hak (LP2M IAIN Palopo, 2026)
This study assesses the fairness of stock prices for issuers that consistently remained constituents of the IDX ESG Leaders (ESGL) during 2020-2024 and examines indications of an ESG premium. The method applies relative valuation based on five-year averages of Price-to-Earnings (P/E) and Price-to-Book Value (P/B). Fair value is estimated as the five-year average P/E multiplied by the latest EPS and the five-year average P/B multiplied by the latest BVPS, then consolidated as the base scenario. The sample comprises 17 issuers with normalized official data. The results show that all issuers are classified as undervalued under the base scenario, indicating multiple compressions and no systematic ESG premium. The findings confirm the usefulness of a concise, transparent, and replicable five-year P/E-P/B framework, while highlighting the need to standardize ESG-financial linkages and strengthen historical multiple data infrastructure. ESG issuers contribute to structural transformation through energy efficiency, low-carbon innovation, and stronger governance that enhances competitiveness and attracts sustainable financing. This study is descriptive and point-in-time; further research is recommended to add non-ESG benchmarks, extend the horizon, and explore alternative multiples.